Kepemimpinan Transformasional, Motivasi Kerja dan Performa Kerja Karyawan ; Systematic Literature Review - Hafid Gisen Parastra; Yunia Wardi; Ilham Thaib (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the effect of transformational leadership and motivation on employee performance. The research method used is systematic literature review (SLR), which is a systematic review of various articles (literature) related to research variables. The results showed that 15 (75%) studies showed a significant relationship between transformational leadership and work performance, 10 (50%) studies showed a significant relationship between transformational leadership and work motivation, 8 (40%) showed a significant relationship between work motivation and work performance, and 2 (10%) indicate that transformational leadership can influence work performance by mediating work motivation. In conclusion, that transformational leadership influences motivation where the better the implementation of transformational leadership in organizations/institutions/institutions, the more employee motivation increases. Keywords: Transformational Leadership, Work Motivation, Work Performance